2013
DOI: 10.1186/cc12738
|View full text |Cite
|
Sign up to set email alerts
|

Limits of normality of quantitative thoracic CT analysis

Abstract: IntroductionAlthough computed tomography (CT) is widely used to investigate different pathologies, quantitative data from normal populations are scarce. Reference values may be useful to estimate the anatomical or physiological changes induced by various diseases.MethodsWe analyzed 100 helical CT scans taken for clinical purposes and referred as nonpathological by the radiologist. Profiles were manually outlined on each CT scan slice and each voxel was classified according to its gas/tissue ratio. For regional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 22 publications
(32 reference statements)
4
63
0
Order By: Relevance
“…The lung cranio-caudal diameter was 250 (234–276) mm, the number of slices analyzed in the subset with interleave of 20 mm was 12 (12–14), while the current-time product was 229 (201–303) mAs. These three findings were similar to those observed in animal scans, and to the values reported in a study describing the limits of normality of quantitative CT [8]. …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The lung cranio-caudal diameter was 250 (234–276) mm, the number of slices analyzed in the subset with interleave of 20 mm was 12 (12–14), while the current-time product was 229 (201–303) mAs. These three findings were similar to those observed in animal scans, and to the values reported in a study describing the limits of normality of quantitative CT [8]. …”
Section: Resultssupporting
confidence: 90%
“…Slice thickness is a known factor affecting the assessment of aeration compartments, in particular hyper-aerated tissue [23, 26, 27]. There is no unanimous consensus concerning which slice thickness should be preferred for the quantitative analysis of lung aeration [5]: several research groups used 5 mm [8] or 1 mm [17] slices. In spiral scans, thicker slices result in a lower number of images to be segmented to perform analysis, and this might explain why many research groups avoided using thinner slices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies found a relevant amount of hyperaerated lung parenchyma among healthy patients [9], as well as a dramatic effect of reconstruction parameters on the evaluation of severe emphysema [10]. Thus, a standardized and reproducible evaluation of hyperaeration by CT is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…We defined the "extent" of lung inhomogeneities as the fraction of the lung volume whose inhomogeneities were >1.61, which represents the 95th percentile of the inhomogeneities computed in normal subjects [4,18].…”
Section: Determination Of Lung Inhomogeneitymentioning
confidence: 99%